(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
This article examines the problem of commonality between humanism and literature. Considerable attention is paid to the problem of the difference between philosophy and literature. As a result of a detailed analysis, similarities and differences were identified.